Women’s Power and Stereotype Denial in Pocahontas Movie - Afri Aryangga; Ely Nurmaily (TEKNOSASTIK, 2017)
The aim of this research is to explicate the women power around men and oppose the stereotype issues of woman who is better taking care than man who is better taking charge. In some cultures, woman is expected to be the caregivers, soft, weak, which are considered feminine attributes and man is expected to be the breadwinners, strong and powerful, which is seen as masculine traits. The object of this research is from Disney’s animation movie, Pocahontas. This movie shows the woman’s power by how the main character protected family and also society, moreover the stereotype denial also is seen by the main character in several extreme activities inside of the movie.